2013
DOI: 10.1007/s12639-013-0315-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal helminth parasites of equids from organized farms of Mumbai and Pune

Abstract: A total of 1,304 faecal samples of different species of equids were examined for presence of helminthic eggs from five different centres in Mumbai and Pune regions of Maharashtra state from October 2011 to June 2012. Overall prevalence of helminthic infestation was found to be 20.63 % with higher rate of occurrence in monsoon (31.29 %) followed by winter (20.40 %) and summer (14.23 %). Four species of nematodes viz. strongyles (10.81 %), Strongyloides westeri (13.19 %), Parascaris equorum (0.23 %) and Dictyoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
9
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 9 publications
4
7
9
4
Order By: Relevance
“…However, as the cold and dry conditions are comparatively unfavourable for the development of parasitic stages leading to lower infection rates in these seasons. Similar variations in seasonal prevalence had been earlier reported by several workers (Sengupta and Yadav 1998;Singh et al 2012;Matto et al 2013).…”
Section: Resultssupporting
confidence: 89%
“…However, as the cold and dry conditions are comparatively unfavourable for the development of parasitic stages leading to lower infection rates in these seasons. Similar variations in seasonal prevalence had been earlier reported by several workers (Sengupta and Yadav 1998;Singh et al 2012;Matto et al 2013).…”
Section: Resultssupporting
confidence: 89%
“…Further, Singh et al (2012) found 75.73% which is higher than the results of the present study. They have found that out of total 532 faecal samples examined, 394 were positive with a prevalence of 74.06 per cent which differs from findings of Matto et al (2013) who have reported as 38.79%. The reason for this increase may be attributed to the large number of animals taken under study by them.…”
Section: Prevalence Of Gastrointestinal Nematodecontrasting
confidence: 72%
“…These findings tallied with the results obtained by (Singh et al, 2012) they have reported the higher intensity of infection in monsoon (79.35%), summer (69.23%) while it was lowest in winter (59.70%). Matto et al (2013) found the overall prevalence of helminthes as 20.63% with higher rate of occurrence in monsoon (31.29%) followed by winter (20.40%) and summer (14.23%) (Strongyloides (13.19%) and Parascaris equorum (0.23%). On the other hand, Sengupta and Yadav, 1998 have mentioned high rainfall, optimum temperature and high relative humidity favour the development and survival of the infective larvae in and around the region of study.…”
Section: Seasonmentioning
confidence: 99%
“…in horses from Rajasthan. But Matto et al (2013) reported very low incidence of 1.3 % Amphistomes spp. infection in horses of Maharashtra, region.…”
Section: Resultsmentioning
confidence: 94%